2012
DOI: 10.1177/0961203312444772
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and fatigue in systemic lupus erythematosus

Abstract: Objective: The objective of this study is to investigate the relationship of oxidative stress to fatigue in systemic lupus erythematosus (SLE). Methods: Patients with a confirmed diagnosis of SLE by ACR criteria and healthy controls completed validated questionnaires to assess depression and fatigue. Fatigue was measured with the Fatigue Severity Scale (FSS) and the Profile of Fatigue (Prof-F). Visual analogue scales (VAS) were also used to assess fatigue and pain. Depression was measured with the Center for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
2
10
0
2
Order By: Relevance
“…A positive correlation between F 2 -isoprostane and fatigue was observed in SLE patients and it was observed that F 2 -isoprostane predicts higher FSS scores in SLE patients. F 2 -isoprostane is currently acknowledged as the most reliable measure of in vivo oxidative stress [36]. The results from this study provide further evidence of an association between oxidative stress and the development of fatigue.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…A positive correlation between F 2 -isoprostane and fatigue was observed in SLE patients and it was observed that F 2 -isoprostane predicts higher FSS scores in SLE patients. F 2 -isoprostane is currently acknowledged as the most reliable measure of in vivo oxidative stress [36]. The results from this study provide further evidence of an association between oxidative stress and the development of fatigue.…”
Section: Resultssupporting
confidence: 66%
“…They observed that fatigued SLE patients had higher levels of F 2 -isoprostane than non-fatigued SLE patients [36]. A positive correlation between F 2 -isoprostane and fatigue was observed in SLE patients and it was observed that F 2 -isoprostane predicts higher FSS scores in SLE patients.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Levels of F2-Isoprostanes in plasma and urine samples have been shown to correlate with in vivo oxidative stress in a number of studies in SLE patients. Studies from Avalos (95 SLE patients), Segal group (71 SLE patients) and Abou-Raya (60 SLE patients) have shown that F2 isoprostane levels are associated with increased disease activity, fatigue and lower quality of life [31,33,91]. …”
Section: Reviewmentioning
confidence: 99%
“…Порушення балансу між концентрацією активних форм кисню (АФК) і компонентів антиоксидант-ної системи (АОС) призводить до оксидативно-го стресу, окисного пошкодження ДНК, білків та ліпідів [29]. Помірне зростання рівня АФК активує ферментативну ланку АОС.…”
Section: оригінальні дослідженняunclassified